Nadia Naveau : Let's play it by ear - Huvenne, Paul; Olyslaegers, Jeroen; Wood, Jon; Naveau, Nadia; Warande (Cultural center : Turnhout, Belgium) ([Lichtervelde] : Hannibal, 2022)
Nadia Naveau blends seriousness with play, and her ability to seduce viewers, while evoking a sense of strangeness is unmatched. Let's Play it by Ear is not only a retrospective of twenty years of artistic practice, but also, like her sculptures, a visual puzzle of materials and references to the past and present.
This sculptural imagination of Nadia Naveau -- You should be dancing -- Nadia Naveau : painting with sculpture -- List of works -- Biography.
Chiefly illustrated.
Catalog of an exhibition held at De Warande, Turnhout, Belgium, December 12, 2021-April 3, 2022.
kunstcatalogus
Keywords: Naveau, Nadia